Displaced intracapsular neck of femur fractures in the elderly: Bipolar hemiarthroplasty may be the treatment of choice; a case control study. Issue 10 (October 2015) - Jonas, S.C.; Shah, R.; Al-Hadithy, N.; Norton, M.R.; Sexton, S.A.; Middleton, R.G.
Abstract Management of the mobile elderly patient who sustains an intra-capsular neck of femur fracture remains controversial. Current evidence is mixed as to whether total hip arthroplasty (THA), which confers higher surgical and dislocation risk, is significantly superior in function and in reduced rates of reoperation when compared to bipolar hemi-arthroplasty. A group of 110 patients with an intra-capsular NOF fracture who had undergone either THA or Bipolar hemi-arthroplasty and were still alive at the time of follow up were retrospectively identified and matched using the National Hip Fracture Database. Matching criteria included ASA, age, sex, pre-op mobility, pre-op AMTS and source of admission. Follow up was by postal questionnaire. Mean follow up was 24 months in both groups (Range; Bipolar 12–36 months, THA 12-38 months). There was no significant difference in pre-operative Tonnis grade, postoperative Oxford Hip Score (OHS) or Short Form 36 (SF-36) scores between the two groups. 12 dislocations in 5 patients occurred in the THA group and none in the bipolar group. 33/55 Bipolar patients were discharged to their own home compared to 35/55 in the THA group. None of the bipolar hemi-arthroplasties were revised to THA. Higher complication rates were experienced in the THA group with no increase in function.